Pengaruh Likuiditas, Leverage Dan Tata Kelola Perusahaan Terhadap Penghindaran Pajak Pada Perusahaan Sektor Industri Di Bursa Efek Indonesia (BEI) - Dio Jeremia Sembiring; Seprianto Purba; Shaila Pratika Sari; Stephanie Imaylia Napitupulu; An Suci Azzahra (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of liquidity, leverage, and corporate governance on tax avoidance in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research used a quantitative approach with secondary data analyzed through multiple linear regression using SPSS 25. The results show that partially, liquidity (CR) has a significant effect on tax avoidance with a significance value of 0.048, leverage (DER) with 0.010, and corporate governance (BDOUT) with 0.029. Simultaneously, all three variables also have a significant effect on tax avoidance, with an F-value of 5.896 and a significance level of 0.003. These findings indicate that financial structure and corporate governance mechanisms play an important role in influencing corporate tax compliance. Therefore, it is recommended that companies maintain a healthy financial structure and strengthen governance practices to minimize tax avoidance.